Deletion of protein kinase D1 in osteoprogenitor cells results in decreased osteogenesis in vitro and reduced bone mineral density in vivo. (5th February 2018) - Bollag, Wendy B.; Choudhary, Vivek; Zhong, Qing; Ding, Ke-Hong; Xu, Jianrui; Elsayed, Ranya; Yu, Kanglun; Su, Yun; Bailey, Lakiea J.; Shi, Xing-Ming; Elsalanty, Mohammed; Johnson, Maribeth H.; et al.
Abstract: Protein kinase D1 (PRKD1) is thought to play a role in a number of cellular functions, including proliferation and differentiation. We hypothesized that PRKD1 in bone marrow-derived mesenchymal stem cells (BMMSC) could modulate osteogenesis. In BMMSCs from floxed PRKD1 mice, PRKD1 ablation with adenovirus-mediated Cre-recombinase expression inhibited BMMSC differentiation in vitro . In 3- and 6-month-old conditional knockout mice (cKO), in which PRKD1 was ablated in osteoprogenitor cells by osterix promoter-driven Cre-recombinase, bone mineral density (BMD) was significantly reduced compared with floxed control littermates. Microcomputed tomography analysis also demonstrated a decrease in trabecular thickness and bone volume fraction in cKO mice at these ages. Dynamic bone histomorphometry suggested a mineralization defect in the cKO mice. However, by 9 months of age, the bone appeared to compensate for the lack of PRKD1, and BMD was not different. Taken together, these results suggest a potentially important role for PRKD1 in bone formation. Highlights: Loss of PRKD1 inhibits mineralization in mesenchymal stem cells (MSCs) in vitro . Loss of PRKD1 in MSCs does not affect alkaline phosphatase activity in vitro . Osteoprogenitor-specific PRKD1 loss reduces bone mineral density and mineralization. Osteoprogenitor-specific PRKD1 loss affects bone microarchitecture in mice in vivo .